2011
DOI: 10.1126/science.1213789
|View full text |Cite
|
Sign up to set email alerts
|

Revealing Atom-Radical Reactivity at Low Temperature Through the N + OH Reaction

Abstract: More than 100 reactions between stable molecules and free radicals have been shown to remain rapid at low temperatures. In contrast, reactions between two unstable radicals have received much less attention due to the added complexity of producing and measuring excess radical concentrations. We performed kinetic experiments on the barrierless N((4)S) + OH((2)Π) → H((2)S) + NO((2)Π) reaction in a supersonic flow (Laval nozzle) reactor. We used a microwave-discharge method to generate atomic nitrogen and a relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
109
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(113 citation statements)
references
References 39 publications
3
109
0
1
Order By: Relevance
“…N 2 itself is produced by atomic nitrogen reactions with small neutral radicals (Daranlot et al 2012;Le Gal et al 2014) which experimental and theoretical studies have shown to be less efficient than previously assumed (Daranlot et al 2012;Daranlot et al 2013;Daranlot et al 2011;Jorfi & Honvault 2009;Loison et al 2014a;Ma et al 2012 (Vigren et al 2012) which is nonetheless sufficient to make this process the major source of NH radicals in current gas-phase astrochemical models (Le Gal et al 2014). Reaction (R1) is problematic due to the endothermicity of the N + + para-H 2 (p-H 2 ) reaction (Zymak et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…N 2 itself is produced by atomic nitrogen reactions with small neutral radicals (Daranlot et al 2012;Le Gal et al 2014) which experimental and theoretical studies have shown to be less efficient than previously assumed (Daranlot et al 2012;Daranlot et al 2013;Daranlot et al 2011;Jorfi & Honvault 2009;Loison et al 2014a;Ma et al 2012 (Vigren et al 2012) which is nonetheless sufficient to make this process the major source of NH radicals in current gas-phase astrochemical models (Le Gal et al 2014). Reaction (R1) is problematic due to the endothermicity of the N + + para-H 2 (p-H 2 ) reaction (Zymak et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…which are barrierless (Daranlot et al 2011;Bergeat et al 2009) and therefore rapid at the low temperatures of interstellar clouds. NO is formed from nitrogen atoms and hydroxyl radicals through reaction (1) and becomes a major intermediate in the synthesis of N 2 through reaction (2).…”
Section: Formation Of No In O-rich Csesmentioning
confidence: 99%
“…The astrophysical interest of reactions between free radicals has motivated an ample list of recent studies of collisions between open-shell atoms such as C( 3 P), [1][2][3][4][5][6][7] N( 4 S), [8][9][10] F( 2 P), [11][12][13][14] O( 3 P), [15][16][17][18] or S( 3 P) (Refs. 19 and 20) with the hydroxyl radical OH( 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent examples of the possibilities of such approaches have been reported for the N+OH reaction. 9,10 In those works, quasi-classical trajectory (QCT) and quantum mechanical (QM) calculations were performed to obtain reaction probabilities, cross sections, and rate constants. A comparison with measured rate constants was also presented in Ref.…”
Section: Introductionmentioning
confidence: 99%